The formalisation of small-scale mining in Chile: achievements and challenges of the National Mining Company (ENAMI) - Scholvin, Sören; Atienza, Miguel (Investigaciones Geográficas, 2023)
Almost 45 million people work in small-scale mining around the world, most of them informally and in very peripheral regions. This article analyses the formalisation of the sector in Chile by the National Mining Company –better known as ENAMI, the acronym of its Spanish name. Based on 19 semi-structured interviews and information from secondary sources, the authors explain that ENAMI not only regulates the sector, which is essential for its legalisation. The organisation also connects local networks of small-scale mining to international markets because it buys, processes and sells the mining output. ENAMI develops the sector, providing credits, geological studies, training programmes and other forms of support. It stabilises the prices of minerals, increasing the resilience against external shocks. Thus, ENAMI has an essential impact on territorial development. However, this model suffers from certain shortcomings. ENAMI needs a much higher annual budget. It has not managed to increase the competitiveness of small-scale mining. The authors discuss different ideas regarding a reform of ENAMI. The organisation could continue to support all small-scale mining companies, keeping them afloat. Alternatively, the focus could shift to increasing competitiveness, which would be a fundamental change of the current model because it implies that firms that do not become more productive will cease to exist.